Studies on Schismatoglottideae of Borneo XV - A Second Species of Bakoa - Wong, Sin Yeng (The Japanese Society for Plant Systematics, 2011)
Bakoa brevipedunculata is newly combined as a second species of the Bornean endemic genus Bakoa (Araceae: Schismatoglottideae), based on Hottarum brevipedunculatum. A new generic delimitation to Bakoa and a key to the species of Bakoa are presented.